2009
DOI: 10.1111/j.1600-0501.2009.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of maxillary sinus septa on reformatted computerised tomography scans

Abstract: This study found a higher prevalence of patients with maxillary sinus septa than what has been reported previously. This may be due to the exact nature of the CT software and the ease of use of the 3D reconstruction for identification of septa. Another explanation could be that all septa that were visible on the 3D reconstruction were included and there was no minimum cut-off height. No significant differences were found between edentulous and dentate patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 10 publications
1
25
1
4
Order By: Relevance
“…With regard to the number of septa, 34.5% of the cases studied by us had one septum; 27.5%, two septa; 8%, three septa; 0.5%, four septa; and 1.5%, five septa. Our results are in accordance with a similar report that 71% of the edentulous patients, as well as 66% of the toothed patients, had at least one septum [18].…”
Section: Resultssupporting
confidence: 94%
“…With regard to the number of septa, 34.5% of the cases studied by us had one septum; 27.5%, two septa; 8%, three septa; 0.5%, four septa; and 1.5%, five septa. Our results are in accordance with a similar report that 71% of the edentulous patients, as well as 66% of the toothed patients, had at least one septum [18].…”
Section: Resultssupporting
confidence: 94%
“…Another factor that contributed to the sample loss was the inclusion criteria. These factors certainly decreased the discriminating power of the study; however, based on other studies, it seems that the sample size was adequate, if certain criteria are observed.…”
Section: Discussionmentioning
confidence: 90%
“…14 While previous studies have evaluated the anatomical structures and variations of the maxillary sinus, to our knowledge this is the first study evaluating whether or not a relation exists among the anatomical variations of the maxillary sinus; Underwood's septa, schneiderian membrane thickness, and the cortical thickness of the inferior border of the maxillary sinus. [17][18][19][20] According to Vlasiss and Fugazzotto, 21 perforation occurs more frequently during osteotomy than during the reflection of the membrane. 1,4,5,15,16 It is reported that the prevalence of antral septa varies between 13 and 35.3% in studies based on the number of sinuses, and between 21.6 and 66.7% in studies based on the number of patients.…”
Section: Discussionmentioning
confidence: 99%